For these types of problems, plug the value inside the ( ) into the (x) of the equation.
g (-3), g (x) = 2x-2
g (x) = 2 (-3) - 2 = -6 - 2 = -8
g (-3) = -8
The answer is B.) one
Hope this helps :)
To do this problem you would first need to factor out a variable, which in this case I would want to do the first equation because it is isolated. Now the equations would look like this:
x = -2y - 1
4x - 4y = 20
Since we know that x is now equal to -2y - 1 we can plug it in to the x value in the second equation:
4 (-2y -1) - 4y = 20
-8y -4 - 4y
-12y - 4 = 20
-12y = 24
y = -2
Now that we know the y value plug the y value to one equation to find the x, I will be using the first equation
x + 2(-2) = -1
x - 4 = -1
x = 3
Solutions:
y = -2
x = 3